Importance of zinc roofs in Paris and their impact on urban runoff pollutant loads - Gromaire, M.C.; Waintrop, N.; Chebbo, G.; Constant, A. (4th International Conference on Innovative Technologies in Urban Drainage (NOVATECH 2001), 2001)
Previous research on the Marais catchment in Paris demonstrated the very high zinc and cadmium contamination of runoff from zinc roofing. Thus further investigations were aimed at evaluating the relative importance of this type of roofing in Paris and its potential contribution to zinc and cadmium loads in wet weather flows. According to these results, about 40% of the surface of roofs in Paris is covered with rolled zinc (1016 ha), and this proportion is not likely to vary significantly in the next years, due to architectural rules. The Zn and Cd concentrations measured in runoff from these roofs are in accordance with literature data on zinc corrosion rates, in the presence of SO2. On an annual scale, runoff from Parisian zinc roofs produces around 34 to 64 metric tonnes of zinc and 15 to 25 kg of cadmium, which is approximately half the load generated by runoff from total Paris.